2022
DOI: 10.3390/microorganisms10030571
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol Ability and Production of Volatile Organic Compounds as a Potential Mechanism of Action of Olive Endophytes against Colletotrichum acutatum

Abstract: Olive anthracnose, mainly caused by Colletotrichum acutatum, is considered a key biotic constraint of the olive crop worldwide. This work aimed to evaluate the ability of the endophytes Aureobasidium pullulans and Sarocladium summerbellii isolated from olive trees to reduce C. acutatum growth and anthracnose symptoms, and to assess A. pullulans-mediated changes in olive fruit volatile organic compounds (VOCs) and their consequences on anthracnose development. Among the endophytes tested, only A. pullulans sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…(E)-2-Octenal is widely present as a flavoring substance in a variety of plants (Cheng et al 2020 ; Ebert et al 2022 ; Raffo et al 2018 ), and previous results have shown that plant-produced (E)-2-octenal causes severe perturbation of the lipid fraction of bacterial plasma membranes and inhibits the activity of microorganisms such as rhizospheric fungi and Candida (Battinelli et al 2006 ; Trombetta et al 2002 ). A recent publication (Sdiri et al 2022 ) found a significant increase in 6-methyl-5-hepten-2-one levels in olive plants after inoculation with S epia acuminata , and the authors speculated that 6-methyl-5-hepten-2-one may play a role in pathogen infection. Page et al (Page et al 2014 ) found that flowers of Silene latifolia and Silene dioica hybrids released 6-methyl-5-hepten-2-one and influenced pollinator preference.…”
Section: Discussionmentioning
confidence: 99%
“…(E)-2-Octenal is widely present as a flavoring substance in a variety of plants (Cheng et al 2020 ; Ebert et al 2022 ; Raffo et al 2018 ), and previous results have shown that plant-produced (E)-2-octenal causes severe perturbation of the lipid fraction of bacterial plasma membranes and inhibits the activity of microorganisms such as rhizospheric fungi and Candida (Battinelli et al 2006 ; Trombetta et al 2002 ). A recent publication (Sdiri et al 2022 ) found a significant increase in 6-methyl-5-hepten-2-one levels in olive plants after inoculation with S epia acuminata , and the authors speculated that 6-methyl-5-hepten-2-one may play a role in pathogen infection. Page et al (Page et al 2014 ) found that flowers of Silene latifolia and Silene dioica hybrids released 6-methyl-5-hepten-2-one and influenced pollinator preference.…”
Section: Discussionmentioning
confidence: 99%
“…Endophytic PGPMS, along with growth promoting [126][127][128][129][130][131][132][133] also plays a pivotal role in maintaining plant resilience to diseases [95,123,126,127,129,132,[134][135][136][137][138][139][140][141][142][143][144][145][146][147] and abiotic stressors [22,24,66,90,121,139,143,148]. Some endophytes also have the potential to control insects [147,149,150] and nematodes [62], as well as combined biotic and abiotic stresses [62,[151][152][153].…”
Section: Microbial Endophytes-induced Stress Tolerance/resistancementioning
confidence: 99%
“…Generally, these microbes live within plant tissues and provide useful metabolites for plant growth and tolerance to stress, including plant pathogens [13,173]. Volatile organic compounds could also be used to control plant diseases [174]. The genus Trichoderma also includes endophytic species that can be exploited as mycoparasites, as in the case of coffee leaf rust caused by Hemileia vastatrix [175].…”
Section: Biocontrol Agentsmentioning
confidence: 99%